Penyesuaian diri siswa kelas VII di sekolah menengah pertama - Tjeriawan, Chenrika Arabella; Sukmawati, Indah (Counseling and Humanities Review, 2023)
Adjustment is important for students of class VII at school. Phenomenon in the field, students are required to follow school rules and adapt in the school environment. New students can only interact and communicate with known classmates and friends. The aim of the research is to look at the description of students' self-adjustment in class VII. Quantitative research method with a descriptive approach. The sample in this study were 53 students with a sampling technique that is simple random sampling. Collecting data using a self-adjustment questionnaire with a Likert scale model. To see a picture of student self-adjustment using the percentage analysis formula. The results of the study found a description of students' self-adjustment in the moderate category with a percentage of 33.96%. This means that SMPS Bina Satria Medan students are able to adjust to the school environment.